Mechanical and Microstructural Characteristics of High-Strength Self-Compacting Concrete (HSSCC) with Optimal Silica Fume and Fly Ash Cement Replacement - Ahmed Aliyu Azare; Bin Wan Ibrahim, Mohd Haziman; Faisal Alshalif, Abdullah; Putra Jaya, Ramadhansyah; Nindyawati Nindyawati (International Journal of Sustainable Construction Engineering and Technology, 2024)
AbstractThis paper focuses on high-strength self-compacting concrete (HSSCC) characteristics with the optimal percentages of cement replacers, fly ash, and silica fume. The aim is to compare all the differing ratios of HSSCC mixtures with the aim of determining their durability. In the initial part of the study, the maximum proportion of these materials the system should include was calculated with the help of the statistical software Minitab. Then, variable silica fume, fly ash, and W/C ratio functions were investigated using response surface methodology at Minimum, Medium, and Maximum levels. The principle of RSM made it possible to identify the composition sets of silica fume, fly ash, and W/C ratio to further assess the possibility of simultaneous optimization. These aspects entailed fresh properties’ verification, slump flow, T500, J-ring, segregation resistance, and compressive strength on newly incorporated properties. The research was undertaken with cement replacements by 05% silica fume, 10% and 15%silica fume, and 20 % and 30% fly ash. Mechanical characteristics such as compressive strength, tensile strength, flexural strength, and properties related to durability, such as water absorption and porosity, were also studied. It was also observed that the best-performing mix was obtained with 5% silica fume and 20% fly ash by the quantity of cement with a water-binder ratio of 0.33. This mixture had the best mechanical properties and the maximum compressive strength, which increased by 27% compared to the essential mix containing only OPC. Furthermore, the porosity and water absorption were reduced by 50% and 55%, respectively, compared to the identical standard mix. Therefore, this HSSCC mix can improve the concrete performance to an extent.